PERBANDINGAN PENANGANAN HUTANG PIUTANG DI BANK BNI SYARIAH DAN BAITUL MAAL WAT TAMWIL FAJAR - Kusnandar, Enan; Midisen, Kisanda; Rahmadani, Sekar Ayu (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
To deal with problems related to sources of funds or capital is the bank. Currently, people are more interested in Islamic institutions. Both Islamic banks and BMTs are shariah. In this study the authors found two institutions that have differences in the handling of accounts payable. Therefore, the author is interested in finding out more about the differences between the two institutions. The purpose of this study is to find out the differences in how to handle accounts payable. To find out the difference in the way of handling accounts payable to customers who died and customers who were affected by the disaster, To find out how the Islamic perspective in handling accounts payable. Al-Qardh is property that is cut to help people in need and then returned to the debtor in full as he received it. In this study there are differences in the handling of accounts payable. This research includes descriptive qualitative research that focuses intensively on a particular object to study it as a case and reveals events or facts, circumstances, phenomena, variables and circumstances that occurred during the research by writing down what actually happened. The results of this study are the findings of 2 differences between BNI Syariah Banks that use insurance in each of their financing as a protection system to benefit both parties. And KSPPS BMT Fajar does not use insurance in every financing because the BMT thinks that insurance is the same as gambling, the system is gharar. However, from the two institutions, the implementation is in accordance with sharia principles. Based on the research, it can be concluded that there are differences in the handling of accounts payable in the protection system at BNI Syariah Bank while BMT Fajar does not use a protection system. However, both institutions are in accordance with Islamic law.